2016
DOI: 10.1007/s00253-016-7609-2
|View full text |Cite
|
Sign up to set email alerts
|

A thermostable GH26 endo-β-mannanase from Myceliophthora thermophila capable of enhancing lignocellulose degradation

Abstract: The endomannanase gene em26a from the thermophilic fungus Myceliophthora thermophila, belonging to the glycoside hydrolase family 26, was functionally expressed in the methylotrophic yeast Pichia pastoris. The putative endomannanase, dubbed MtMan26A, was purified to homogeneity (60 kDa) and subsequently characterized. The optimum pH and temperature for the enzymatic activity of MtMan26A were 6.0 and 60 °C, respectively. MtMan26A showed high specific activity against konjac glucomannan and carob galactomannan, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 64 publications
0
21
0
1
Order By: Relevance
“…2, D273, the acid/base proton donor) (Kumagai et al 2011). Whereas bacterial β-mannanases mainly belong to the GH5 and GH113 families (Fusco et al 2018;Zang et al 2015), the more acid-tolerant and catalytic efficient fungal β-mannanases are grouped into the GH5 and GH26 families (Do et al 2009;Hakamada et al 2014;Harnpicharnchai et al 2016;Katsimpouras et al 2016;Liao et al 2014;Naganagouda et al 2009;Wang et al 2015;Yu et al 2015) (Table 2). More recently, the identification of Man134A, produced by the filamentous fungus Aspergillus nidulans, led to the establishment of the new family of GH134 in the CAZy database (Shimizu et al 2015).…”
Section: β-Mannanasesmentioning
confidence: 99%
“…2, D273, the acid/base proton donor) (Kumagai et al 2011). Whereas bacterial β-mannanases mainly belong to the GH5 and GH113 families (Fusco et al 2018;Zang et al 2015), the more acid-tolerant and catalytic efficient fungal β-mannanases are grouped into the GH5 and GH26 families (Do et al 2009;Hakamada et al 2014;Harnpicharnchai et al 2016;Katsimpouras et al 2016;Liao et al 2014;Naganagouda et al 2009;Wang et al 2015;Yu et al 2015) (Table 2). More recently, the identification of Man134A, produced by the filamentous fungus Aspergillus nidulans, led to the establishment of the new family of GH134 in the CAZy database (Shimizu et al 2015).…”
Section: β-Mannanasesmentioning
confidence: 99%
“…CBM1 is known to confer cellulose binding and increase the mannan hydrolysis of complex substrates such as softwood and ivory nut extractions containing both mannan and cellulose [ 27 , 28 ]. Fungal GH26 endomannanases may have a CBM35 [ 24 , 29 ], a CBM family known to bind to β -mannans, uronic acids and α- d -galactopyranosyl residues on carbohydrate polymers [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The available literature in particular includes several studies with the Trichoderma reesei GH5 endomannanase, ( Tres Man5A) [ 3 , 4 , 17 , 32 ], but also of other endomannanases [ 33 ]. A few studies have shown increased glucose release from wood substrates when cellulase (and xylanase) cocktails have been supplemented with fungal GH26 endomannanases [ 29 , 34 ], but a comparison of the performance of several different endomannanases on the same softwood substrate is not available in the literature. Severe pretreatment methods, leaving only small amounts of mannan in the pretreated substrate, are generally used on softwood to allow enzymatic saccharification.…”
Section: Introductionmentioning
confidence: 99%
“…3c). After directed evolution, the optimal pH of m Rm Man5A is much lower than those of many wild-type β-mannanases from Bacillus subtilis (pH 6.5) [32], Myceliophthora thermophila (pH 6.0) [33], and Thermobifida fusca (pH 8.0) [34]. Although the optimal condition of m Rm Man5A still can not reach the level of several wild-type β-mannanases, such as rMan5P1 (pH 4.0, 80 °C) [20], Man5A2 (pH 4.0, 90 °C) [21], and MAN-P (pH 4.5, 80 °C) [35], the specific activities of these β-mannanases are significantly lower than that of m Rm Man5A at their optimal conditions (Table 1).…”
Section: Discussionmentioning
confidence: 99%